Knee joint kinematics of support leg during maximal instep kicking in female soccer players - Sakamoto, K. (ISBS Proceedings Archive (Michigan), 2020)
The purpose of this study was to investigate the effect of knee motion of support leg during maximal instep kicking on female soccer players. Their kicking motions were recorded by a motion capture system. The range of motion of knee angle (knee variation) was caluculated. There were significant negative relationships of foot velocity with knee variation (r =0.73, p < 0.05). The participants were divided into small (n = 8) and large (n = 8) variation groups based on their change amount of support leg knee angle during forward swing. Foot velocity, vertical hip velocity of kicking leg, and vertical centre of pelvis displacement during forward swing phase of small knee variation group than those of large variation group were found significant differences (p < 0.05). These results suggested that training for female players should focus on reducing knee angular displacement (flexion) of support leg during forward swing phase in instep kicking.